Characteristic of composite bioplastics from tapioca starch and sugarcane bagasse fiber: Effect of time duration of ultrasonication (Bath-Type) - Asrofi, Mochamad; Salit, Mohd Sapuan; Ilyas, R. A.; M., Ramesh (Elsevier, 2021)
Composite bioplastic is an alternative solution to solve the plastic waste problem in our environment. This is due to the composite bioplastic is one material that is environmentally friendly and easily degraded in nature. This study aims to make composite bioplastic from environmentally friendly materials, namely tapioca starch and sugarcane bagasse fiber (SBF). The addition of SBF into the tapioca matrix serves as a structural reinforcement of composites bioplastics. SBF was added by 1 wt% (from dry weight of starch basis) and kept constant for each variation of the sample. The fabrication of composite bioplastic using the solution casting method. The variation time duration of ultrasonication on composite bioplastic (tapioca starch and 1 wt% bagasse fiber) includes 0, 5, 10 and 15 min. Tensile testing, observation of fiber morphology, fracture surface characteristics, moisture absorption rate were carried out conducted by tensile test, scanning electron microscope (SEM), and moisture absorption test, respectively. The results show that the addition of ultrasonication increases the tensile strength of composite bioplastic samples. The highest tensile strength value was achieved by a sample with 15 min ultrasonication for 2.5 MPa. This result was supported by fracture morphology which shows a compact structure. In addition, the moisture absorption rate also decreases with increasing ultrasonication. Preparation and giving ultrasonication on composite bioplastic samples was highly recommended for improving the properties of the sample.